Polish republican discourse in the sixteenth century - Pietrzyk-Reeves, Dorota (2020)
"Exploring republican ideas and concepts that developed in sixteenth-century Poland under the impact of humanism and the Renaissance, as well as political and constitutional changes, this is a landmark study of republican discourse in sixteenth-century Poland- Lithuania. It provides a conceptual and contextual analysis of the rich political literature and debate which animated intellectual life and political reasoning during the Polish-Lithuanian Commonwealth and effectively demonstrates its republican character